2013
DOI: 10.1074/jbc.m113.510362
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 130-kDa Smooth Muscle Myosin Light Chain Kinase Expression by an Intronic CArG Element

Abstract: Background: Mechanisms regulating transcription of MLCK are poorly defined. Results: Deleting a CArG element from the mylk1 gene specifically decreased expression of the 130-kDa smMLCK isoform, resulting in decreased intestinal contractility and proliferation. Conclusion: The 130-kDa smMLCK isoform has functions that cannot be compensated for by the 220-kDa MLCK. Significance: Floxed mylk1 mice permit specific functions of the 130-kDa smMLCK to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
2
12
1
1
Order By: Relevance
“…This finding should be contrasted with an earlier report showing near abolishment of CNN1, another SMC-restricted gene product (34), upon CRISPR-mediated editing of a single intronic CArG box (17). Similarly, a decrease in expression of smooth muscle myosin light chain kinase with attenuated intestinal smooth muscle contractility was noted after deletion of an upstream CArG box (35). The absence of change in LMOD1 expression with the double CArG box mutation suggests that, whereas proximal promoter CArG boxes are sufficient for Lmod1 promoter activity (12), they are not necessary in their native genomic context, which would imply that other, more distal CArG boxes coordinate SRF-dependent expression of LMOD1 in both human and mouse.…”
Section: Discussioncontrasting
confidence: 54%
“…This finding should be contrasted with an earlier report showing near abolishment of CNN1, another SMC-restricted gene product (34), upon CRISPR-mediated editing of a single intronic CArG box (17). Similarly, a decrease in expression of smooth muscle myosin light chain kinase with attenuated intestinal smooth muscle contractility was noted after deletion of an upstream CArG box (35). The absence of change in LMOD1 expression with the double CArG box mutation suggests that, whereas proximal promoter CArG boxes are sufficient for Lmod1 promoter activity (12), they are not necessary in their native genomic context, which would imply that other, more distal CArG boxes coordinate SRF-dependent expression of LMOD1 in both human and mouse.…”
Section: Discussioncontrasting
confidence: 54%
“…Due to the protracted time in generating genetically altered mice with this traditional approach, coupled with the complexity and redundancy of gene regulation, there have been far fewer regulatory knockouts as compared to genic knockouts. Further, genic control regions, such as enhancers, have almost always been deleted via Cre recombinase-mediated excision of 100s-1000s of nucleotides, effectively leaving a genomic cavity 2123 . While these studies certainly provide some insight into the role of enhancers in target gene expression and animal pathophysiology, they lack resolution in narrowing down specific elements within the enhancer that mediate gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Notch1-induced HRT2 can lead to repression of both Notch and myocardin function through destabilization of respective transcription complexes. Of note, a recent study identified a functional CArG element within intron 15 of SM-MLCK that selectively regulates 130 kDa MLCK isoform expression required for contractile activity in visceral smooth muscle (28). Whether the intronic CArG is additionally sensitive to Notch signals remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid Constructs-Expression plasmids for intracellular Notch1 (pcDNA3-ICN1), flag-tagged myocardin (pFLAGmyocardin) and MLCK-luciferase reporter constructs (p6476 and p389) were described previously (14,26,28). Expression plasmids for wild-type HRT2 (pHRT2-V5) and HRT2 mutants (HRT2:BHO, HRT2:BHOϩ, and HRT2[B-]) were described previously (26,29).…”
Section: Methodsmentioning
confidence: 99%